2009
DOI: 10.1007/s00259-009-1289-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and 123I-FP-CIT SPECT imaging in drug-induced parkinsonism and Parkinson’s disease

Abstract: DIP and PD are difficult to differentiate based on clinical signs. The precision of clinical diagnosis could be reliably enhanced by (123)I-FP-CIT SPECT imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 21 publications
1
33
1
5
Order By: Relevance
“…Such a drug-exacerbated parkinsonism may represent patients at a prodromal state of PD who do not tolerate the offending medication. Furthermore, it has concordantly been reported that in patients suspected of having drug-induced PS who, however, presented with pathologic DAT binding, either neurodegenerative PS alone or a combination of neurodegenerative and drug-induced PS was finally determined to be present (45,(59)(60)(61).…”
Section: Drug-induced Psmentioning
confidence: 63%
“…Such a drug-exacerbated parkinsonism may represent patients at a prodromal state of PD who do not tolerate the offending medication. Furthermore, it has concordantly been reported that in patients suspected of having drug-induced PS who, however, presented with pathologic DAT binding, either neurodegenerative PS alone or a combination of neurodegenerative and drug-induced PS was finally determined to be present (45,(59)(60)(61).…”
Section: Drug-induced Psmentioning
confidence: 63%
“…In FTD patients, where neuroleptics are widely used to assist with behavior disorders, it is important to differentiate between Parkinsonism with underlying neurodegenerative pathology and a drug-induced syndrome. The uptake of tracer is normal in drug-induced Parkinsonism, and an abnormal image supports the diagnosis of dopaminergic system neurodegeneration [82]. Unfortunately, neuroimaging of the dopaminergic system has cannot differentiate between PD and atypical Parkinsonism well [77].…”
Section: Neuroimaging In Ftd With Parkinsonismmentioning
confidence: 99%
“…Algunos estudios han comprobado que este grupo, además de la retirada del fármaco, se beneficia del tratamiento con levodopa 8,17 , por lo que su identificación precoz es importante. Desgraciadamente, la similitud clínica existente entre un parkinsonismo iatrogénico puro (PY) y un parkinsonismo neurodegenerativo 8,[18][19][20] , incluido el PSEF, dificulta la identificación solo con aquella, por lo que, en muchas ocasiones, se hace necesario recurrir a pruebas complementarias para establecer el diagnóstico.…”
Section: Introductionunclassified
“…En la actualidad, la tomografía por emisión de fotón simple con 123 Ioflupano, también conocida como SPECT [ 123 I]FP-CIT o DaT-SCAN, es la prueba de referencia para el diagnóstico diferencial entre PRF y otros parkinsonismos neurodegenerativos 8,18,19,[21][22][23] . El PY aparece como consecuencia del bloqueo que los fármacos provocan en los receptores dopaminérgicos, sin que la vía estriatonígrica se vea afectada y, por tanto, sin que se altere la captación del radiotrazador [17][18][19][24][25][26] .…”
Section: Introductionunclassified
See 1 more Smart Citation